Evaluation of Teacher's Ability in Using Technology Distance Learning in Banda Aceh City - Muslem Daud; Mariati MR (JURNAL SERAMBI ILMU, 2022)
The Covid-19 disaster has prompted the adjustment of the learning process at various levels of education from basic to tertiary levels. The adjustments of the teachers to the disaster included the use of Distance Learning (PJJ). Therefore, a research was conducted that aimed at how prepared the teacher was in the use of the intended PJJ technology; case study of learning during the covid-19 period in Banda Aceh. The research sample of primary school teachers and madrasah Ibtidaiyah amounted to 55 people. Data collection tools are interviews and questionnaires containing statements with answers provided. The data were analyzed using the percentage method. The results of the study indicate that in general school/madrasah teachers have limitations in using online software for the learning process. Even though the teachers have good readiness manually in preparation for learning, they have not  able yet to compile well in soft copy as learning material to be presented in PJJ. Therefore, continuous training and mentoring is needed so that teacher competence continues to increase, especially in the use of technology for PJJ.